2021
DOI: 10.1021/acs.jpca.0c11539
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron Spectroscopic and ab Initio Computational Studies of the Anion, HThO

Abstract: The synergetic combination of anion photoelectron spectroscopy and highlevel relativistic coupled-cluster calculations was employed to study the anion, HThO − . The atomic connectivity of this anion was found to be HThO − and not ThOH − . Vibrational and electronic energy spacings in the HThO − photoelectron spectrum were measured and calculated, with good agreement between them being found. Computations yielded electronic energies and equilibrium structures as well as enabling orbital analyses. The adiabatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Studies on smaller actinide clusters provide tremendous insights into the nature of actinide bonding. However, our understanding is still limited regarding An–TM clusters. Analogous to the theoretical studies investigating the similarities of actinide–platinum complexes with their actinide–oxygen analogs, gold has been suggested as an isolobal analog to both hydrogen and the halogens, as it has the highest electron affinity of the metals and has been shown to have highly ionic character in bonding. Comparison of the photoelectron spectra of Au n – with their analogous Au n –1 H – counterparts shows noteworthy similarities, which led to the earliest notion of hydrogen-like behavior of gold . Wang and co-workers showed that gold has halogen-like behavior in TiAu 4 and hydrogen-like behavior in Si–Au. , Gagliardi reported that gold is halogen-like in several systems, including actinide–tetraauride systems. , Recently, due to similarities in the photoelectron spectra of Au 2 F n – and AuF n +1 ( n = 1 or 2), DFT calculations have given insights into experimental evidence for the halogen-like behavior of gold .…”
Section: Introductionmentioning
confidence: 99%
“…Studies on smaller actinide clusters provide tremendous insights into the nature of actinide bonding. However, our understanding is still limited regarding An–TM clusters. Analogous to the theoretical studies investigating the similarities of actinide–platinum complexes with their actinide–oxygen analogs, gold has been suggested as an isolobal analog to both hydrogen and the halogens, as it has the highest electron affinity of the metals and has been shown to have highly ionic character in bonding. Comparison of the photoelectron spectra of Au n – with their analogous Au n –1 H – counterparts shows noteworthy similarities, which led to the earliest notion of hydrogen-like behavior of gold . Wang and co-workers showed that gold has halogen-like behavior in TiAu 4 and hydrogen-like behavior in Si–Au. , Gagliardi reported that gold is halogen-like in several systems, including actinide–tetraauride systems. , Recently, due to similarities in the photoelectron spectra of Au 2 F n – and AuF n +1 ( n = 1 or 2), DFT calculations have given insights into experimental evidence for the halogen-like behavior of gold .…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of early actinoids (An) currently attracts the intense interest of many inorganic chemistry groups around the world, with most studies being devoted to U. Despite the existence of only one oxidation state (IV; however, there are a few exceptions), the chemistry of Th is equally interesting. , The main reason for this is its use as a new nuclear energy source. , Other reasons for the great interest in the chemistry of Th include the bioinorganic and theoretical chemistry aspects, topics related to chemical bonding issues, ,, the properties of Th-based metal–organic frameworks (MOFs), , the light emission of some Th­(IV) complexes with aromatic Schiff bases, Th­(IV)-mediated unusual reactions, the reactivity of this metal ion with redox-active ligands, the replacement of the paramagnetic U IV by Th IV in mixed-metal U IV /d compounds for the independent study of the magnetic exchange interactions between the transition-metal ions, understanding the scarcity of Th­(IV)-peroxido clusters, and so on.…”
mentioning
confidence: 99%